CODE CHOICE IN SOCIOLINGUISTICS - Nailuz Zakiyatul Mahmudah; Khoirotul Illmi; Asya Ian Ramadani; Muh. Hasan Gibran Bugis Abdullah (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This article discusses the phenomenon of code choice in sociolinguistics, which refers to how individuals select a language or language variety in specific social contexts. Code choice is influenced by various factors, including social background, communication situations, and speaker identity. Through qualitative data analysis, this article explores how code choice reflects social and cultural dynamics in multilingual societies. The findings indicate that code choice not only serves as a communication tool but also as a reflection of social identity and power relations.